2005
DOI: 10.1111/j.1399-3038.2005.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of atopy in infancy: The KOALA Birth Cohort Study

Abstract: The aim of the KOALA Birth Cohort Study in the Netherlands is to identify factors that influence the clinical expression of atopic disease with a main focus on lifestyle (e.g., anthroposophy, vaccinations, antibiotics, dietary habits, breastfeeding and breast milk composition, intestinal microflora composition, infections during the first year of life, and gene-environment interaction). The recruitment of pregnant women started in October 2000. First, participants with Ôconventional lifestylesÕ (n ¼ 2343) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
137
2
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 126 publications
(145 citation statements)
references
References 25 publications
1
137
2
5
Order By: Relevance
“…The majority of these alternative respondents have an explicit preference for healthy nutrition (e.g. vegetarian, organic (30) ), while they do not have specific pronounced opinions regarding PA, as far as we know. The fact that recruitment channel was found to be a significant positive predictor of the healthy intake pattern score (b 5 0?24; P , 0?001) supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these alternative respondents have an explicit preference for healthy nutrition (e.g. vegetarian, organic (30) ), while they do not have specific pronounced opinions regarding PA, as far as we know. The fact that recruitment channel was found to be a significant positive predictor of the healthy intake pattern score (b 5 0?24; P , 0?001) supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy pregnant women were recruited from an existing cohort, as well as through 'alternative lifestyle' recruitment channels (e.g. anthroposophist midwives, organic food shops) (30) . The latter group (17?9 %) could have an alternative lifestyle with regard to dietary habits (e.g.…”
Section: Respondents and Proceduresmentioning
confidence: 99%
“…[17][18][19] A description of the selection of the study populations is provided in the Methods section in this article's Online Repository at www. jacionline.org.…”
Section: Study Populationsmentioning
confidence: 99%
“…From October 2000 onwards, healthy, pregnant women (n 2343) were recruited at midwives' practices in the southern part of the Netherlands participating in an ongoing prospective cohort study on Pregnancy-Related Pelvic Girdle Pain (12,13) . That study did not use lifestylerelated inclusion criteria and the participants showed good comparability with the general population (12) (general population recruitment group).…”
Section: Study Design and Participantsmentioning
confidence: 99%